Two microporous MOFs constructed from different metal cluster SBUs for selective gas adsorption1. Issue 75 (28th September 2015) - Li, Yun-Wu; Xu, Jian; Li, Da-Cheng; Dou, Jian-Min; Yan, Hui; Hu, Tong-Liang; Bu, Xian-He
<x xml:space="preserve">Abstract</x> Two microporous MOFs have been constructed from different metal cluster SBUs. Both PMOFs exhibit highly selective uptake for CO2 over CH4 and N2 owing to abundant active sites.